Business Law Perspective in The Protection of The Old City as A Cultural Reserve Area - Terry Febriken, Adrianus; Paulus, Darminto Hartono (Journal of Private and Commercial Law, 2021)
Kota Tua is a cultural heritage area that needs conservation. This area has old buildings that need protection and preservation. Protection and preservation of old buildings in the Old City of Jakarta is the responsibility of the Department of Tourism and Culture of DKI Jakarta as stipulated in Local Regulation No. 10 of 2008 concerning Regional Device Organization in Article 62 paragraph (2), concerning the task of organizing tourism and cultural affairs. The purpose of writing this law is to know how the local government in protecting old buildings and to know the problems and efforts of the local government in protecting old buildings in the Old City area of Jakarta. The authors in his study used normative juridical methods to collect data by reviewing or analyzing secondary data. while the data processing techniques used are by qualitative methods. Conservation is an effort made by the Department of Tourism and Culture of DKI Jakarta in protecting and preserving old buildings in the Old City area of Jakarta. The Implementation Unit of the Activity as the executor of the service function is difficult to execute conservation activities so it must work with the Private Consortium Company and the Restoration Council Team to still be able to participate in the implementation.